Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12877-021-02127-8
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index, performance on activities of daily living and cognition: analysis in two different populations

Abstract: Background With this study, we aim to determine the associations of the different categories of the body mass index (BMI) with activities of daily living (ADL) and cognitive performance in two different populations living in the community; Colombian and South Korean older adults. Methods We performed a cross-sectional analysis of two surveys separately; The Survey on Health, Well-Being, and Aging in Colombia (SABE) (n = 23,343) and the Korean Longi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
4
6
0
Order By: Relevance
“…Weight loss regarded as a side effect of depression symptoms, the risk of shifting from normal BMI to underweight status increased by 62% among participants with depression symptoms in our study, which was consistent with another population-based study of adults in the United Kingdom that depressed mood was able to predict an unhealthy weight loss ( 27 ). Moreover, ADL impairment was associated with a higher risk of transitioning from normal to overweight, which matched most previous findings, among which, a study that found being overweight but not obese was associated with better daily functioning in the Colombian population ( 28 ). In summary, to move public health toward precision in public health, the specific risk factors related to transition intensity for different BMI statuses were explored to determine if personalized treatments could prevent unhealthy weight change.…”
Section: Discussionsupporting
confidence: 88%
“…Weight loss regarded as a side effect of depression symptoms, the risk of shifting from normal BMI to underweight status increased by 62% among participants with depression symptoms in our study, which was consistent with another population-based study of adults in the United Kingdom that depressed mood was able to predict an unhealthy weight loss ( 27 ). Moreover, ADL impairment was associated with a higher risk of transitioning from normal to overweight, which matched most previous findings, among which, a study that found being overweight but not obese was associated with better daily functioning in the Colombian population ( 28 ). In summary, to move public health toward precision in public health, the specific risk factors related to transition intensity for different BMI statuses were explored to determine if personalized treatments could prevent unhealthy weight change.…”
Section: Discussionsupporting
confidence: 88%
“…It is important to note that about 73% of our population was either overweight or obese compared to <50% in Zhang et al, which may explain why we did not find the same relationship between these variables. A report looking at Colombian and South Korean populations supported our findings and showed no association between BMI and cognition, (Borda et al, 2021) indicating that ethnic background could influence the association between BMI and cognition, even more so than obesity.…”
Section: Discussionsupporting
confidence: 77%
“…It is important to note that about 73% of our population was either overweight or obese compared to <50% in Zhang et al, which may explain why we did not find the same relationship between these variables. A report looking at Colombian and South Korean populations supported our findings and showed no association between BMI and cognition, (Borda et al, 2021) indicating that ethnic background could influence the association between BMI and cognition, even more so than obesity. Management of T2D involves a complex regimen requiring various degrees of cognitive pliability; and as such, cognitive impairments are associated with reduced T2D self-management and ability to complete tasks such as personal and day-to-day activities (American Diabetes Association, 2018; Smith et al, 2014) which may worsen glycemic control.…”
Section: Discussionsupporting
confidence: 73%
“…Some studies found a protective effect of BMI increase on cognitive function ( 6 , 24 ). In contrast, other studies found unfavorable, mixed, or no significant impact of BMI increase for different BMI ranges ( 25 , 26 ). The findings of heterogeneous BMI effects varying by BMI value indicate the presence of asymmetric effects of BMI rather than a single impact in either the positive or negative form.…”
Section: Discussionmentioning
confidence: 76%